An intrinsic connection between COVID-19 and aging - Jingchao Wang; Jonathan Wei; Fabin Dang; Hiroyuki Inuzuka (Acta Materia Medica, 2023)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) caused a rapidly spreading outbreak of coronavirus disease 2019 (the COVID-19 pandemic). COVID-19 has severely affected healthcare systems worldwide, as well as the global economy, and has significantly increased morbidity and mortality rates. The majority of COVID-19-related deaths occurred in older individuals, primarily among those with concomitant diseases, including metabolic, respiratory, and cardiovascular diseases. Aging hallmarks, such as cellular senescence, chronic inflammation, and genomic instability, partially explain the increased disease severity at the molecular level with advancing age. Other multifactorial considerations, including healthcare facilities, socioeconomic status, and dissemination of epidemic information, may help control morbidity in the elderly population. While the World Health Organization declared an end to the emergency status of COVID-19 in May 2023, physical and emotional impairments may persist after recovery from the virus. Precautions should therefore be taken to prevent future pandemics, and suitable emphasis should be placed on addressing persistent COVID-19 and preventing future pandemics.